Proposing Directions for Completing the University Training Program to Meet Output Standards at Pham Ngoc Thach University of Medicine - Võ Thị Thanh Hương; Hồ Nguyễn Anh Tuấn (Journal of Technical Education Science, 2025)
Currently, with the remarkable advancements in technology, economics, and society, along with the increasingly high demands from businesses for newly graduated students, universities are facing the challenge of improving the quality of education. To achieve this goal, a comprehensive change is needed in the capabilities of lecturers, teaching methods, learning models, and the learning environment. In addition to enhancing the professional competence of lecturers, applying modern and flexible teaching methods, universities in Vietnam also need to invest in equipment and restructure their training programs. Restructuring training programs not only meets urgent needs but also ensures the expected learning outcomes for students. An important task in the current curriculum restructuring process is shifting from a content-based (Content Based) approach to an outcome-based (OBE - Outcome-Based Education) approach. This article will share some aspects of the characteristics of OBE and propose adjustments to the training programs at Pham Ngoc Thach University Of Medicine in order to improve the quality of teaching, learning, and ensure overall quality